2011
DOI: 10.1016/j.bbrc.2010.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of cardiomyocytes activates mitochondrial matrix metalloproteinase causing electrical remodeling

Abstract: Cardiac arrhythmias, instigated by mechanical and electrical remodeling, are associated with activation of extracellular matrix metalloproteinases (MMPs). However, the connection between intracellular MMPs activation and arrhythmogenesis is not well established. Previously, we determined localization of MMP in the mitochondria using confocal microscopy. We tested the hypothesis that electrical pacing induces the activation of mitochondrial MMP (mtMMP) and is associated with myocyte mechanical dysfunction. Myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Cytochrome c leaks into the cytosol, and Bax translocates into the mitochondria ( 9 , 10 ). Data presented here show increased active MMP-9 in the mitochondria and its capillary cells in hyperglycemic conditions, and these results are in agreement with the results from others showing association of active mitochondrial MMP-9 with mechanical dysfunction of cardiac myocytes ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Cytochrome c leaks into the cytosol, and Bax translocates into the mitochondria ( 9 , 10 ). Data presented here show increased active MMP-9 in the mitochondria and its capillary cells in hyperglycemic conditions, and these results are in agreement with the results from others showing association of active mitochondrial MMP-9 with mechanical dysfunction of cardiac myocytes ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were also observed in another cell-based therapy for dilated cardiomyopathy in a rat model (Sun et al 2009). Invitro studies also suggested that abnormal pacing or homocysteine treatment of isolated myocytes resulted in enhancement of mMMP-9 and myocyte dysfunction (Moshal et al 2009; Vacek et al 2011). Together, these studies suggest that abnormal mitochondrial biogenesis or enhanced oxidative stress in the mitochondria contribute to abnormal activation of MMP-9 and lead to degradation of important myocyte couplers such as Cx-43.…”
Section: Mitochondria In Heart Diseasementioning
confidence: 99%
“…Electrical stimulation of cardiac cells was investigated by many research groups in both macro-and microscale (Cheng et al, 2006, Au al., 2007, Barash et al, 2010, Maidhof et al, 2012, Tandon et al, 2011, Vacek et al, 2011, Kujala et al, 2012, Boudou et al, 2012. Next to features such as culture medium perfusion, the presence of hemoglobin via oxygen carriers in the culture medium or the acting of cyclic stretch, electrical field stimulation is the most important to mimic heart tissue.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 96%